PEMBENTUKAN BUDAYA ORGANISASI BERKELANJUTAN: INTEGRASI NILAI-NILAI LINGKUNGAN DALAM PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA - Husnah, Rif'atul; Izzah, Ismatul (Edumanajerial : Journal of Educational Management, 2023)
The establishment of a Sustainable Organizational Culture is a major concern in an increasingly complex and sustainable business era. This study analyzes the implementation of environmental values in human resource management practices as an effort to create a sustainable organizational culture. Through in-depth case studies of organizations that integrate environmental values in their human resource management processes, this study aims to explore the impact of these changes on the overall organizational culture. The research method involved interviews with key stakeholders, direct observation, and analysis of relevant documents. The results of the study highlighted the challenges and opportunities organizations face in adopting environmental values in their human resource management practices. It was found that the integration of environmental values not only increases environmental awareness among employees, but also forms the foundation for a sustainability-focused organizational culture. This research provides an in-depth insight into how organizations can achieve sustainability through the integration of environmental values in human resource management. Practical implications and strategic recommendations are outlined to assist organizational leaders and human resource practitioners in guiding cultural transformation towards sustainability in this changing era.